Mobile community learning programme's effectiveness in case management for psychiatric nurses: A preliminary randomised controlled trial. (February 2020) - Liu, Wen-I; Liu, Chien-Hung; Liao, Chang-Yen; Chao, Pei-Ru; Chu, Kuo-Chung
Abstract: Background: The global health care system has applied case management (CM) as a care delivery service provided by nurses. Nurses require continuing education in CM to enhance their professional knowledge and competence. Mobile communities have been used to promote continuing education for medical professionals. However, limited studies have examined the effectiveness of such learning programmes in CM for psychiatric nurses. Objective: To evaluate the effectiveness of a mobile community learning (MCL) programme in CM for psychiatric nurses. Design: This study used an experimental two-group pre- and post-test design. Settings and participants: Psychiatric nurses employed in a psychiatric teaching hospital situated in northern Taiwan were recruited. Methods: Nurses were randomly allocated to the experimental or comparison group. The former participated in the learning intervention in CM. The CM knowledge index and a competence scale were used to determine outcomes. Pre-tests and 2-month pos t -tests were conducted. The MCL programme comprised five simulated learning modules, self-assessment questions, learning cases, learning resources and experience sharing. A two-way repeated-measures analysis of variance was performed to evaluate the effect of the intervention on target outcomes. Results: The questionnaires were completed by 48 participants. The two groups possessed high homogeneity with regard to characteristics and pre-test outcomes. Differences between the two groups regarding CM knowledge (F = 22.99, p < .01) and competence ( F  = 6.33, p = .015) were significant. The programme had a positive benefit on the learning experience in the experimental group; the mean satisfaction score for the programme reached 4.27 (range, 1–5). Conclusions: MCL programmes for psychiatric nurses can effectively enhance CM knowledge and competence. However, these methods cannot completely replace the continuing education approach for achieving CM competence.